The effect of radical cystectomy on survival in patients with metastatic urothelial carcinoma of the urinary bladder. Issue 7 (28th September 2019) - Luzzago, Stefano; Palumbo, Carlotta; Rosiello, Giuseppe; Pecoraro, Angela; Deuker, Marina; Tian, Zhe; Shariat, Shahrokh F.; Saad, Fred; de Cobelli, Ottavio; Karakiewicz, Pierre I.
Abstract: Background: To test the effect of radical cystectomy (RC) with chemotherapy vs only chemotherapy on overall mortality (OM) in metastatic urothelial carcinoma of the urinary bladder (mUCUB). Methods: Within the Surveillance, Epidemiology, and End Results registry (2004–2016), we identified patients with mUCUB. Stratification was made according to treatment: RC with chemotherapy vs only chemotherapy. Kaplan‐Meier plots and multivariable Cox regression models were used before and after 1:1 propensity score (PS) matching and inverse probability of treatment weighting (IPTW). Results: Of 2414 patients with mUCUB, 500 (21.0%) vs 1914 (79.0%) were treated with RC with chemotherapy vs only chemotherapy, respectively. In multivariable Cox regression models, RC with chemotherapy was associated with lower OM in the overall cohort (hazard ratio [HR], 0.5; P < .001), after 1:1 PS matching (HR, 0.5; P < .001), after IPTW (HR, 0.5; P < .001) and after accounting for number and location of metastases (HR, 0.5; P < .001). However, higher overall survival after RC with chemotherapy was only observed in patients with one metastatic site (21 vs 16 months; P = .001). Conclusion: In contemporary patients with mUCUB, RC with chemotherapy is associated with lower OM rates, relative to chemotherapy alone, but only in patients with a single metastatic site. These individuals accounted for the vast majority of patients in whom an RC was performed, despite the presence of metastatic disease.